Towards a tourism development zone for ancient city of Mrauk-U and its environs - Win, Myint (2008)
The ancient city of Mrauk-U is one of the most attractive tourist destinations in Myanmar. Among the ancient city of Myanmar, the ancient city of Mrauk-U still retains its richness in art and architecture of religious monuments. Now, the inventory list of ancient monuments shows that there are 157 ancient monuments around Mrauk-U. Majority of ancient monuments except a few were built of stone. Many stupas and temples were ruined by heavy rain or by bombing during the Second World War. Similarly many stupas and temples were destroyed by treasure hunters who are in search of antiquities and valuable jewellery. On the other hand, the ancient city lacks proper tourist facilities as well as communication and transportation facilities. The aim of the paper is to revive the historic atmosphere of the ancient city of Mrauk-U by preserving and restoring ancient monuments and establishment of efficient tourist facilities to attract more tourists. Then, creation of further tourism facilities which fit into the tourism products, handicraft development and physical control with the development of human settlements and activities are necessary. The main objective of the paper is to develop tourism in the historic city of Mrauk-U area is a controlled manner. If unplanned, the ancient city could lead to uncontrolled development which would quickly degrade the religious monuments, the natural resources and the cultural fabric of the ancient city. To safeguard the sound future development of tourism in the historic area of Mrauk-U, it is essential that the local residents be integrated into all programmes and that their social and economic welfare improve alongside increasing tourist activity.